THE EFFECTIVENESS OF MATHEMATICAL LEARNING IN LOGIC COMPETENCY WITH PROBLEM BASED LEARNING THROUGH THE COOPERATIVE MODEL OF TYPE THINK-PAIR-SHARE IN TERM OF STUDENT ACHIEVEMENT AND STUDENT CONFIDENCE OF GRADE X SMA NEGERI 1 DEPOK - Indri Aryanti; Sahid . (Universitas Negeri Yogyakarta, 2017)
The purpose of this research were to describe the effectiveness of mathematical learning in logic competency with problem based learning through the cooperative model of type think pair share (TPS) in term of student achievement and student confidence. This research used quasi-exsperimental with pre-test and post-test control group design. Its population was all students of grade X SMA Negeri 1 Depok. The samples were class XD as experiment class which given problem based learning through the cooperative model of type TPS and class XB as control class whivh given conventional learning approach. The instruments used in this research were learning instrument, i.e. lesson plan and student worksheet, pre-test and post-test as test instrument to measure student achievement, observation sheets and questionnaire confidence as non-test instrument. The hypotheses testing used were one sample t-test and independent sample t-test. The results indicated that: (1) mathematics learning with problem based learning through the cooperative model of TPS was effective in terms of student achievement, (2) mathematics learning with conventional learning approach was effective in terms of student achievement, (3) mathematics learning with problem based learning through the cooperative model of TPS was not effective in terms of student confidence, (4) ) mathematics learning with conventional learning approach was not effective in terms of student confidence, and (5) mathematics learning with problem based learning through the cooperative model of TPS was not more effective than mathematics learning with conventional learning approach in terms of student achievement.